Grammar Learning Strategies by Chinese Language Education Students: A Lesson from Grammar Courses - Wijaya, Ratna Wulan; Sitaresmi, Dhatu; Sukaton, Ounu Zakiy (Journal of Language and Literature Studies, 2025)
The complexities of Chinese grammar make it quite challenging to become proficient in. To help learners in mastering grammar, using the right grammar learning strategy can help them to improve their language proficiency. The aims of this study are to investigate the frequency of using Chinese grammar learning strategies, identify the differences in the use of strategy types by students majoring in Chinese Language Education class of 2022 and 2023 at Ma Chung University, and identify the differences in strategies used by male and female students. This research classified as descriptive quantitative. The research instrument used a questionnaire, was developed based on the Grammar Learning Strategy Inventory by Miroslaw Pawlak. Based on the results of the study, it was found out that respondents more frequently used social strategies (mean= 3.59) when learning Chinese grammar; the class of 2022 students more frequently used metacognitive strategies (mean=3.73),  while class of 2023 students more frequently used social strategies (mean=3.48); furthermore, male students more frequently used social strategies (mean=3.77), while female students more frequently used metacognitive strategies (mean=3.65). More specifically, this study suggests that teachers should focus more on facilitating their students through various interactions, as this is the most frequently used approach in social strategies. As for this study, grammar learning strategies in the Chinese language is very important and must be developed further.